Public-private partnership as a mechanism of education management in the structure of the social and investment model of economic growth - Dzhikiya, Meri K.; Karp, Marina V.; Bart, Tatyana V.; Kukushkin, Sergey N. (Frontiers in Education, 2023)
The goal of this research was to find the influence of each mechanism of financial management of education – in the structure of the social and investment model of economic growth – on the results in the sphere of its development: quality, quantitative accessibility, and development of digital skills with students. The study’s methodological approach involved the economic and mathematical modelling of (with the help of regression analysis) of the contribution of alternative investment mechanisms to the development of digital skills of the economically active population. We compared the contribution of isolated public and private investments to public-private partnership and proved its preference. We determined the place of the mechanism of education management based on public-private partnership in the structure of the social and investment model of economic growth. It was determined that the only manifestation of higher education's development, which largely depends on financial support, is digital skills among the active population. The connection between digital skills among the active population and investments in higher education by the terms of public-private partnership is clear (regression – 0.47 points). An increase in the share of public-private partnership in the structure of financing of the development of higher education by up to 90% allows increasing digital skills among the active population from 61.49 points to 94.54 points – i.e., by 53.75%.